P-Selectin sustains extramedullary hematopoiesis in the Gata1 low model of myelofibrosis - Martelli, Fabrizio; Zingariello, Maria; Spangrude, Gerald; Lewandowski, Daniel; Marra, Manuela; Sancillo, Laur; Rana, Rosa; Migliaccio, Anna (Italian Journal of Anatomy and Embryology, 2015)
Splenomegaly is a major manifestation of primary myelofibrosis (PMF) contrib- uting to clinical symptoms and hematologic abnormalities. The spleen from PMF patients contains increased numbers of hematopoietic stem cells (HSC) and megakar- yocytes. These megakaryocytes express high levels of P-selectin (P-sel) that, by trig- gering neutrophil emperipolesis, may cause TGF-β release and disease progression. This hypothesis was tested by deleting the P-sel gene in the myelofibrosis mouse model carrying the hypomorphic Gata1low mutation that induces megakaryocyte abnormalities that recapitulate those observed in PMF. P-selnullGata1low mice survived splenectomy and lived three months longer than P-selWTGata1low littermates and did not express fibrosis and osteosclerosis in the marrow or splenomegaly. Furthermore, deletion of P-sel disrupted megakaryocyte/neutrophil interactions in spleen, reduced TGF-β content and corrected the HSC distribution that in Gata1low mice, as in PMF patients, is abnormally expanded in spleen. Conversely, pharmacological inhibition of TGF-β reduced P-sel expression in megakaryocytes and corrected HSC distribution. Spleens, but not marrow, of Gata1low mice contained numerous cKITpos activated fibro- cytes, probably of dendritic cell origin, whose membrane protrusions interacted with megakaryocytes establishing niches hosting immature cKITpos hematopoietic cells. These activated fibrocytes were not detected in spleens from P-selnullGata1low or TGF-β-inhibited Gata1low littermates and were observed in spleen, but not in marrow, from PMF patients. Therefore in Gata1low mice, and possibly in PMF, abnormal P-sel expres- sion in megakaryocytes may mediate the pathological cell interactions that increase TGF-β content in MK and favor establishment of a microenvironment that supports myelofibrosis-related HSC in spleen.